Economic Impact and Coping Mechanisms of Small and Medium-Sized Enterprises (S.M.E.s) in Nigeria during Currency Redesign - Aladejebi, Olufemi; Oladimeji, Johnson Abiodun; Bukola, Amao-Taiwo (Archives of Business Research, 2023)
On October 26, 2022, the Central Bank of Nigeria (CBN) introduced a redesign of the N1, 000, N500, and N200 Naira currency notes to promote a cashless economy. Despite the well-intentioned government initiative, this policy posed significant challenges to Small and Medium Enterprises (SMEs) in Nigeria, resulting in decreased sales and productivity. This study aims to assess the impact of the currency redesign on small business performance, gauge awareness and preparedness among SMEs regarding the redesign, explore coping mechanisms employed by SMEs during the currency overhaul in Lagos, Nigeria, and propose enhancements for future currency redesign strategies. Utilizing a structured online questionnaire, primary data was collected from 310 SMEs in the Yaba/Ojuelegba region of Lagos, Nigeria, employing a stratified random sampling technique. Both SPSS and Excel were utilized for data analysis. The findings indicated a considerable awareness of the currency redesign among business owners, yet inadequate preparedness due to limited resources and information. The currency redesign had a negative impact on SMEs, particularly in terms of decreased sales, but had little impact on workforce reductions. Price adjustments and better terms with suppliers were among the coping strategies, with point of sale (P.O.S.) machines emerging as the primary alternative payment method. Increased publicity, extended implementation periods, ample new currency supply, harmonized policies across government branches, alignment of monetary and fiscal policies, and increased implementation flexibility are among the recommendations for improved future implementations.